Agricultural Innovation Action Strategy Based on Community Development - Sujimin, Sujimin; Kolopaking, Lala M; Sjaf, Sofyan (Sodality: Jurnal Sosiologi Pedesaan, 2019)
The development of agriculture innovation tends to be oriented towards the increasing of the farm productivity rather than the equitable distribution living standard for farmer. Thus, the innovations have not only caused the social inequality in villages, but also the inequality of the relationship between rural and urban area. This study emphasizes two objectives, namely to conduct a critical evaluation of an organization that has created many agricultural innovations and to formulates new strategies from the organization to reduce social inequality. The data were gathered using some approaches: literatures study, structured quetionaires interviews, field survey, observation, and focus group discussion. The data collecting was started by reviewing literatures data and continued by interviews to 60 respondents using structured evaluation quetionnaires. The respondents were selected by accident sampling technic. Field survey conducted in the head office of organization, Yayasan Mutiara Keraton Solo (YMKS), Sukamantri Village (Tamansari Sub-District, Bogor Regency) and Sambirejo Village (Plupuh Sub-District, Sragen Regency) started from March to June 2018. In depth interviews were orginised in focus group discussion to 16 informans. The focus group discussion was conducted to construct the strategies of the organizational action in the future. The result of the study indicate that the performance of YMKS, established in 1994, is in a good criteria. However, the YMKS has a business vulnerability that is not continuous if the organization does not find a new strategy to maintan its existence. The organization has come characteristics such as innovative agricultural institution with involving society, social business organization for increasing farm productivity, and institution for citizen development. This study concludes that there are 5 (five) strategies and 4 (four) action programs that should be developed by the YMKS containing basic social values related to the importance of the increasing quantity and quality of human resources carried out together to create the farmer regeneration as youth agricultural innovators. In addition, the strategy and action also include the development of ideas so that actions are carried out on the basis of strengthening for the collaborative network in the “Working Together” shceme to establish Business-Community as a driving factor for community development acitivities. The thesis, however, highlight that this action is a new way of agricultural innovation encouring efforts to overcome social inequality.